Smoking causes colon carcinoma - Colditz, Graham A.; Yaus, Kathleen P. (Cancer, 2004)
In the study by Colangelo et. al., the authors reported their findings regarding the correlation between smoking and mortality from colorectal carcinoma in a cohort of 39,299 subjects with an average of 26 years of follow‐up. The editorial concludes that smoking causes colon cancer and tobacco control should be the highest public health priority. See also pages 288–93.